Drivers of fintech adoption in financial institutions in Bangladesh: a case study on IPDC Finance Ltd - Salam, Sawda (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.